Early Māori photography as commodified object: Mementoes, miniatures and material culture. Issue 2 (1st December 2020) - Conrich, Ian
During the late nineteenth and early twentieth centuries, there was a boom in the different forms of material culture of the photographic image with the emergence of cheap methods for its mass (re)production. The material culture extended into postcards, illustrated books, magic lantern slides and stereoviews, but also into the much-less discussed area of souvenir china. These commodified objects of illustrated porcelain were popular mementoes of places visited, physical reminders of spaces encountered, made possible through newly developing modes of leisure culture and organized travel. Edwardian New Zealand was no exception, where images of the Māori were a striking presence within its visual culture. This was a country that was beginning to promote its cultural uniqueness partly through its Indigenous population, with early tourism literature referring to the country as Maoriland. New Zealand souvenirs depicted images of the Māori and Māoritanga (Māori culture) on decorative china essentially for consumption by local tourists and travellers. This article considers these commodified objects in the context of photography as material culture, exploring their social biography and the manner in which the images were reproduced and altered. It contends that in addressing keepsake china as objects bearing photographic images, and in positioning these souvenirs as popular artefacts within a scopic culture, a more complex argument of variant readings emerges.